Growth patterns of urban Malaysian children under 24 months of age in Selangor, Malaysia - Heng, Yaw Yong; Mohd Shariff, Zalilah; Chee, Yen Wong (Nutrition Society Malaysia, 2023)
Introduction: To identify the growth patterns of young children during the first two years of life according to gestational age, birth weight, and growth status at 24 months of age. Methods: This was a retrospective cohort study of 4,570 young children in Selangor. Data were extracted from children’s health records in government health clinics. Growth data were analysed using the Anthro Plus software that utilises the World Health Organization growth standards. Results: Generally, wasting prevalence was the highest at birth and 24 months, but stunting was more predominant from 1 to 21 months. Weight-for-age z-scores (WAZ), lengthfor-age z-scores (LAZ), and weight-for-length z-scores (WLZ) from birth to 24 months were within -3.00 to 0.00 standard deviation (SD) for pre-term low birth weight children, –1.50 to 0.00 SD for pre-term normal birth weight children, and –2.50 to 0.50 SD for full-term low birth weight children. While WAZ, LAZ, and WLZ from birth to 24 months for underweight/stunted/wasted children were within –2.50 to 0.50 SD, the values for overweight/obese (OV/OB) children were within –1.00 to 2.00 SD. For normal children, WAZ, LAZ, and WLZ exhibited comparable trends, with values within –1.00 to 0.00 SD from birth to 24 months. Conclusion: While stunting and wasting persisted as the most common forms of malnutrition in this sample of young children, the prevalence of OV/OB increased by 24 months. Interventions to promote child growth should focus not only on the prevention of undernutrition, but also on OV/OB.